2007
DOI: 10.1002/pssc.200673720
|View full text |Cite
|
Sign up to set email alerts
|

Raman studies of ferroelectric domain walls in lithium tantalate and niobate

Abstract: PACS 63.20.Dj, 77.84.Dy, 78.30.Hv Using confocal Raman spectroscopy at low temperature we investigated the perturbation of the phonon modes across a domain wall region as a function of sample stoichiometry in lithium tantalate and niobate. For all samples, we found that the Raman spectra were changed. The intensity of the A(LO) phonon modes and most of the E(TO) phonon modes were shifted and changed in their relative intensity over a 20 µm length scale. Our measurements suggest that the intensity of the A(L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…Previous work aimed at studying the properties of domain walls using Raman spectroscopy have shown intensity changes in the Raman spectrum [14-17] and frequency shifts of the bulk crystal Raman peaks in the Raman spectrum [15][16][17][18] near the domain wall. However, most of these effects are associated with intrinsic defects and local charging introduced by the nonstoichiometry of the samples.…”
mentioning
confidence: 99%
“…Previous work aimed at studying the properties of domain walls using Raman spectroscopy have shown intensity changes in the Raman spectrum [14-17] and frequency shifts of the bulk crystal Raman peaks in the Raman spectrum [15][16][17][18] near the domain wall. However, most of these effects are associated with intrinsic defects and local charging introduced by the nonstoichiometry of the samples.…”
mentioning
confidence: 99%
“…It can be assumed that the shift of the E(TO 8 ) band position found in refs. [15] and [16] is related to the growth of the E(TO 9 ) band.…”
Section: Raman Investigation Of the Domain Structurementioning
confidence: 99%
“…Micro-Raman spectroscopy is recently applied to the investigation of the domain structure of PPLN or domain inverted crystals [15,16]. It was found that some parameters (e.g.…”
Section: Raman Investigation Of the Domain Structurementioning
confidence: 99%
“…15 According to the Raman scattering data, 18,32,33 LiNbO 3 has two fundamental transverse optical-phonon frequencies x To and x Te , corresponding to the ordinary and extraordinary waves, respectively. The main behaviors of the permittivities o and e in the 0.1-10 THz frequency range can be fitted by the Lorentz model, 15,17 For plane waves, we set k y ¼ 0 without loss of generality, and explicitly derive k x as…”
mentioning
confidence: 99%
“…In Table I, we list the calculated characteristic quantities at about 100 K. For sensitive THz-photon manipulation, a low temperature is helpful for suppressing the thermal noise or dissipation. 10,11,32,33 In Table I, one can see clearly the huge effective refractive index and ultra-short modal wavelength compared with the free-space wavelength of low-THz photons. Large dissipation occurs at frequencies above 4 THz; whereas below 4 THz, for E F Շ 0:1 eV, the wavelength can indeed be squeezed to 100-200 nm while the confining length is only about 10-20 nm.…”
mentioning
confidence: 99%